1996
DOI: 10.30843/nzpp.1996.49.11416
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of organosilicone surfactant concentration and spray application factors in glyphosate efficacy

Abstract: The interactions between the concentration of an organosilicone, Silwet L-77 ® surfactant, and spray application factors were studied. Uptake of spray solutions via stomata and the herbicidal effects of a sub-lethal rate of glyphosate generally increased with increasing Silwet L-77 concentration (0-0.4%), but the interaction between surfactant concentration and carrier volume (50-800 litres/ha) was highly significant. High surfactant concentrations induced maximal infiltration even at low spray volumes, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…The effect could be exacerbated by either surfactant antagonism due to the agrochemicals formulants (Knoche and Bukovac 1993) or to leaf surface absorption (Buick et al 1993). The current trial and previous studies (Gaskin et al 1996;Ray et al 1986;Vanner and Ray 1988) support to the hypothesis that, for foliage absorbed herbicides, efficacy is highly dependent on surfactant rate per hectare in both laboratory and field conditions. In the aerial spray trials, provided the rate/ha of surfactant was maintained at that recommended for a standard 200 litres/ha application, reducing the application volume to 50 -20 litres/ha did not reduce herbicide efficacy.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The effect could be exacerbated by either surfactant antagonism due to the agrochemicals formulants (Knoche and Bukovac 1993) or to leaf surface absorption (Buick et al 1993). The current trial and previous studies (Gaskin et al 1996;Ray et al 1986;Vanner and Ray 1988) support to the hypothesis that, for foliage absorbed herbicides, efficacy is highly dependent on surfactant rate per hectare in both laboratory and field conditions. In the aerial spray trials, provided the rate/ha of surfactant was maintained at that recommended for a standard 200 litres/ha application, reducing the application volume to 50 -20 litres/ha did not reduce herbicide efficacy.…”
Section: Resultssupporting
confidence: 79%
“…The results clearly show that above-ground tomato dry weight production, following treatment with sub-lethal rates of either glyphosate or metsulfuron, is sensitive to the per hectare rate of herbicide, and per hectare rate of surfactant but not to the per hectare application volume (over the range 50-200 litre/ha). Gaskin et al (1996) showed that height growth of tomatoes, treated with a constant but sub-lethal rate of glyphosate, could be predicted (P<0.0002, R 2 = 75%) by a linear model using total organosilicone dose (rate/ha) over a wider range of application volumes (50-400 litre/ha). Decreasing the percent concentration of organosilicone surfactant can decrease herbicide uptake (Stevens and Zabkiewicz 1990) and efficacy (Balneaves et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…The practical implication of these results is that organosilicone blends, such as Du-Wett and Bond Xtra, are less likely than a pure organosilicone to cause crop damage when used with pesticides which are not intended to penetrate into plants. Infiltration of solutions was consistently greater at the higher application volume for both surfactants (Table 2), an organosilicone effect which is well established (Gaskin et al 1996). This also indicates a potential for greater phytotoxicity with high spray application volumes.…”
Section: Stomatal Infiltrationsupporting
confidence: 58%
“…Infiltration of spray into the stomata of potato leaves was determined using a radiolabelled probe, 14 C-deoxyglucose (Amersham, UK). Droplets (0.24 µl) of solution were applied to an adaxial leaf surface on five separate plants, to approximate spray application rates of 200 and 1000 litres/ha, and infiltration determined at 10 min after treatment as described previously (Gaskin et al 1996).…”
Section: Methodsmentioning
confidence: 99%